Actinic Cheilitis: Analysis of Clinical Subtypes, Risk Factors and Associated Signs of Actinic Damage - Isabel Rodríguez-Blanco; Ángeles Flórez; Carmen Paredes-Suárez; Romina Rodríguez-Lojo; Daniel González-Vilas; Aquilina Ramírez-Santos; Sabela Paradela; Ignacio Suárez Conde; Manuel Pereiro-Ferreirós (Medical Journals Sweden, 2019)
Abstract is missing (Short communication)